PERSEPSI PEGAWAI TENTANG KOMPETENSI MANAJERIAL KEPALA TATA USAHA SMP NEGERI DI KOTA BUKITTINGGI - Mona Filardi; Rifma Rifma (Universitas Negeri Padang, 2020)
The purpose of this research is to see information about the Employee’s Perceptions of the managerial competence of head administration in SMP Negeri di Kota Bukittinggi. This research is a descriptive study. The populations are all employee of SMP negeri di Kota Bukittinggi which totaling are 45 people. The instrument of this research by using a questionnaire using Likert scale model which has proven validity and reliability. The results of this research showed that the average score of at Employee’s Perceptions of the managerial competence of head administration in SMP Negeri di Kota Bukittinggi is 4,03, It can be concluded that Employee’s Perceptions of the managerial competence of head administration in SMP Negeri di Kota Bukittinggi has good.